Recent Studies of Parametrically Excited Mooring Cables for Submerged Floating Tunnels. (2016) - Cantero, Daniel; Rønnquist, Anders; Naess, Arvid
Abstract: Most current designs for Submerged Floating Tunnels (SFT) include a mooring system to fix the position of these floating structures. Long period waves, such as swell waves, parametrically excite the system and might result in excessive vibrations in the cable. This paper presents two distinct studies. First, an analytical investigation of the system's stability is performed to derive a closed-form expression, which allows for a quick evaluation of the system's stability. This expression is obtained through the Harmonic Balance Method (HBM) with two harmonic terms. The contribution of multiple modes of vibration is investigated for the case of small sag to span ratios. The expression is compared with the results from a numerical model, revealing the applicability of the proposed formulation. The second study investigates the tension in the mooring line during parametric excitation. Correct design should avoid excessive forces that might break the line or very small forces that lead to momentarily slack cables. Thus, the aim of this study is to assess the validity of using the stability charts for the design of mooring lines with respect to safe levels of cable forces. This is achieved through the numerical analysis of a cable model using Abaqus. Cable vibrations and cable forces are compared for a range of amplitudes and frequencies of the support motions.